Differential effects of cannabis constituents on schizophrenia-related psychosis: a rationale for incorporating cannabidiol into a schizophrenia therapeutic regimen - Johnson, Kennadi; Weldon, Abby J.; Burmeister, Melissa A. (Frontiers in Psychiatry, 2024)
Schizophrenia is a serious mental health disorder that confers one of the highest mortality rates of all psychiatric illnesses. Although the disorder's psychotic symptoms are treatable with conventional antipsychotics, they remain incurable. Moreover, medication adherence is poor, and individuals with schizophrenia choose to self-medicate with illicit substances, including cannabis. It is well-established that the delta-9-tetrahydrocannabinol (delta-9-THC) component of cannabis elicits psychotomimetic effects at high doses; worsens schizophrenia-related psychosis; commonly develops into cannabis use disorder in individuals with schizophrenia; and increases the risk of earlier-onset schizophrenia symptoms in those harboring genetic susceptibility. However, individuals with schizophrenia commonly use cannabis and cannabis derivatives such as cannabidiol (CBD) component. These products seem to alleviate psychotic symptoms and relieve adverse side effects of antipsychotic medications. Therefore, one notion that has gained traction is the potential utility of cannabis-derived cannabidiol (CBD) as adjunct treatment to reduce schizophrenia-associated psychosis and other symptoms. Currently, preclinical and clinical data remain inconclusive. The present review distinguishes the mechanisms underlying schizophrenia-associated vs. cannabis-induced psychosis; reviews the evidence for delta-9-THC-mediated exacerbation vs. CBD-mediated amelioration of schizophrenia-associated psychosis; and describes potential approaches for incorporating CBD into schizophrenia therapeutic regimen in a safe and efficacious manner.